Nature, raw materials, and political economy - Ciccantell, Paul S., 1965-; Smith, David A.; Seidman, G. (Elsevier JAI, 2005)
The papers in this volume push the study of the multifaceted nature-society relationship and the socioeconomic consequences of human dependence on nature forward in a variety of areas. In the first section, "Theoretical Foundations", the five chapters lay out theoretical models for examining the nature-society relationship. The chapters examine the roles of material process, space, and time in shaping social processes of economic ascent and long term hegemonic change, as well as the role of the analysis of raw materials in environmental sociology. In the second section, "Commodities, Extraction and Frontiers", a series of case studies covering a range of industries, locations and historical periods present a variety of applications of the political economy of natural resources to critical issues regarding commodities, extraction and frontiers.The case study industries include oil, steel, transport, furs, sugar and Brazil nuts, and the chapters examine regions in Latin America, North America, and Asia. In the third section, "Connecting Political and Economic Change", four chapters focus on the relationship between raw materials, economic change, and socioeconomic change. These chapters examine long term economic and political change and the relationship between political and economic change in Latin America and Africa.
Keywords: Natural resources.; Raw materials.; Nature -- Effect of human beings on.; Rural development.; Industrial sociology.; Social impact of environmental issues.; Political Science -- Public Policy -- Environmental Policy.; Business & Economics -- Economics -- General.; elektronické knihy; electronic books